The effectiveness of team building among employees in small and medium enterprises in Malaysia - Lu, Yuying (2023)
This study aimed to determine the effect of the group factor and use of technology on both organizational commitment and personal achievement, the effect of the group factor, use of technology, organizational commitment and personal achievement on the effectiveness of team building among employees in Small and Medium Enterprises (SMEs) in Malaysia, and the mediating effect of personal achievement and organizational commitment in the relationships between group factor and effectiveness of team building, and between use of technology and effectiveness of team building. The study adopted the quantitative approach. The purposive sampling method was employed. A total of 520 employees from selected SMEs in Malaysia were chosen as a sample. The online questionnaire was used as an instrument to gather the data. Structural Equation Modelling (SEM) was used to analyze the data. The findings showed that group factor (GF) and use of technology (UT) have a significant and positive effect on organizational commitment (OC) [GF= 0.173, UT= 0.627, p<0.05, R2=0.381], and personal achievement (PA) [GF=0.325, UT=0.413, p<0.05, R2=0.555]. The findings also revealed the significant positive effect of GF, UT, OC and PA on the effectiveness of team building (ETB) [GF=0.167, UT=0.157, OC=0.192, PA=0.218, p<0.05, R2=0.602]. In addition, the findings demonstrated the mediating effect of OC and PA in the relationship between GF and ETB, as well as the relationship between UT and ETB. In conclusion, to enhance the effectiveness of team building among employees in SMEs, the roles of group factors, use of technology, organizational commitment and personal achievement should be intensified. In implication, the findings provide fresh insights on the components that should be included in designing a better program to enhance the effectiveness of team building among the employees in the SMEs.